The degree to which school principals practice transformational leadership and its relationship to the level of risk and emergency management in schools in The Sultanate of Oman - Al-Buraiki, Ali Hamad; Belaid, Youssef Nait (Journal of Educational and Psychological Sciences, 2025)
The study aimed to reveal the degree of school principals’ practice of transformational leadership and the level of risk and emergency management in the schools of the Sultanate of Oman. It also aimed to reveal the existence of a positive correlation with statistical significance at the significance between the degree of school principals’ practice of transformational leadership and the level of risk and emergency management. The study community consisted of all government school principals in the Sultanate of Oman. The study sample included (241) individuals from the community. The study relied on the descriptive approach as a study method, and the questionnaire was used as a study tool. The study concluded that the general average of the dimensions of the first axis: transformational leadership, came with a response degree of (average), and the general average of the dimensions of the second axis: risk management, came with a response degree of (average). It also showed the existence of a positive correlation with statistical significance at the significance level (0.01) between the degree of school principals’ practice of transformational leadership and the level of risk and emergency management in the schools of the Sultanate of Oman. The study recommended designing specialized training programs for school principals that focus on developing transformational leadership skills, such as inspiration, influence, relationship building, creative thinking, emphasizing the development of a shared vision between the manager and employees, and encouraging participation in decision-making to enhance the management of risks and emergency situations.